Phenomenological Study of Community Experience in Obtaining Services from Aubilee Health Center - Atika Zainab; Wisnu Sadhana; Rizki Yeni Wulandari; Rika Damayanti; Abdullah Abdullah (Indonesian Journal of Global Health Research, 2025)
Puskesmas Pembantu (Pustu) is the spearhead of basic health services in rural areas. However, the effectiveness of Pustu services is often affected by various factors such as the availability of staff, infrastructure, and community accessibility. This study aims to reveal in depth the community's experience in obtaining health services at Pustu. This study used a qualitative approach with a phenomenological study method. The research sample was selected by purposive sampling. Informants consisted of 11 people, namely the general public, cadres, and village officials who were selected purposively. Data collection was conducted through in-depth interviews, and data analysis followed Colaizzi's 7 steps. The study found six main themes: (1) positive and responsive staff attitudes are factors in community satisfaction, (2) limited schedules and staff attendance hamper access to services, (3) inadequate Pustu facilities reduce comfort, (4) referrals to the main Puskesmas are hampered by distance and transportation, (5) community expectations for an active and alert Pustu, and (6) the important role of village government in supporting service continuity. The existence of Pustu is very important for village communities, but service delivery still faces challenges in terms of service continuity, completeness of facilities, and accessibility.